Socioeconomic factors associated with the number of children ever born by married Ghanaian females: a cross-sectional analysis. Issue 2 (8th February 2023) - Boateng, Dennis; Oppong, Felix Boakye; Senkyire, Ephraim Kumi; Logo, Divine Darlington
Abstract : Objective: Most studies in Ghana on determinants of children ever born (CEB) are often conducted among all females of reproductive age and do not adequately report patterns among married females. Considering the importance of marriage to fertility in the Ghanaian context, this study seeks to explore the association of socioeconomic characteristics of married Ghanaian women with CEB. Design: Data from the 2017 Ghana Maternal Health Survey were used. Three separate models were considered: linear regression model using CEB and two logistic regression models. Bivariate and multivariate analyses were considered for all models. Setting: The study was conducted in all 10 administrative regions of Ghana. Participants: Married females aged between 15 and 49 years. Primary and secondary outcome measures: Socioeconomic factors associated with married females' CEB. Results: In all three models, place of residence, zone, wealth index, age, age at marriage, media exposure, level of education, number of abortions and age at first sex were all significantly (p<0.05) associated with CEB. Married females with higher education had lower odds of one or more births and lower odds of giving birth to three or more children. Also, married females from households with the highest wealth index had fewer CEB, lower odds of one or more births and lower odds of giving birth to three or more children. Conclusion: Socioeconomic characteristics of married females in Ghana, including education and wealth status had a significant influence on the number of CEBs. We recommend governments' intervention to help bridge the gaps in access to education and income-generating opportunities. The mass media must be used to propagate and counsel married females on the potential of high fertility and its consequences.